Association between diet quality, nutritional status, and sarcopenia in people aged 80 years or older - Francine Flores Klein; Amanda Guterres Beuren; Vitor Pelegrim de Oliveira; Renato Gorga Bandeira de Mello (Geriatrics, Gerontology and Aging, 2024)
Objective: To investigate the association between diet quality, nutritional status, and sarcopenia in a sample of the oldest old. Methods: Using a cross-sectional design, individuals aged ≥ 80 years were enrolled. To determine their energy and macronutrient intake, 24-hour dietary recall was used to calculate the Healthy Eating Index. Nutritional status was categorized based on Mini Nutritional Assessment (MNA) scores. Sarcopenia was diagnosed using both the 2010 and 2018 EWGSOP criteria. Electrical bioimpedance was used to calculate the muscle mass index. Muscle strength was measured through handgrip dynamometry, and muscle performance was determined with a 4-m gait speed test. To test the association between the HEI with sarcopenia, means of HEI scores were compared between sarcopenic and non-sarcopenic participants using indendent t-tests. Prevalence rate ratios were calculated using a Poisson Regression model with robust estimation of standard errors. Results: The study population consisted of 119 participants, predominantly women (n = 67; 56.3%), with a mean age of 83.4 (SD, 3.0) years. The prevalence of sarcopenia varied significantly according to the classification criteria, being higher according to EWGSOP 2010 than EWGSOP 2018 criteria (46.7 vs. 17.6%), as expected. Female participants and those categorized as malnourished presented higher prevalence of sarcopenia. Nutrition quality, estimated by the Healthy Eating Index, was not associated with the outcome. Reduced total energy and high protein intake were independently associated with both sarcopenia and severe sarcopenia, regardless of the diagnostic criteria. Conclusions: The Health Eating Index was not associated with sarcopenia in this sample of older adults ≥80 years. Sarcopenia prevalence, as defined by the EWGSOP 2018 criteria, was higher in thosewith MNA≤24 and with reduced daily total energy comsumption independently of age, sex and education attainment. Higher protein intake, oposed to expected, was indenpendently associated with sarcopenia, possibly due to protopathic bias. Large longitudinal studies are still required to investigate the relationship between nutrition quality and Sarcopenia in 80+ aged adults.